2002
DOI: 10.1002/gps.615
|View full text |Cite
|
Sign up to set email alerts
|

Post stroke depression, first year post stroke, in middle band patients

Abstract: Post Stroke Depression (PSD) is a frequent and treatable complication of stroke, with significant influence on recovery and mortality (De Weg et al., 1999) but its mechanism is not well understood. While there is some evidence for the organic base of PSD (Robinson et al., 1984), it may also represent an expected emotional reaction to the severe disability imposed by the stroke. The rate of post stroke depression varies according to the mode of assessment between 20% and 70% and therefore it is not clear whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 6 publications
(8 reference statements)
1
10
0
1
Order By: Relevance
“…Patients with post-stroke depressive symptoms were more cognitively impaired. Our finding is in agreement with the results of many previous studies, where a correlation between PSD and cognitive impairment was found [2,3,11,17,20]. Contrary to previous studies [22,42,43], we did not observe differences between the number of aphasic patients in both groups, and we did not analyze the predictive value of aphasia for PSD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Patients with post-stroke depressive symptoms were more cognitively impaired. Our finding is in agreement with the results of many previous studies, where a correlation between PSD and cognitive impairment was found [2,3,11,17,20]. Contrary to previous studies [22,42,43], we did not observe differences between the number of aphasic patients in both groups, and we did not analyze the predictive value of aphasia for PSD.…”
Section: Discussionsupporting
confidence: 91%
“…High level of social functioning was related to lower risk for PSD in a previous study by Shimoda and Robinson [47]. Conversely, Gottlieb et al [2] observed that high rather than low level of social support was associated with PSD. It is difficult to properly define social support and its role in PSD.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Numerous observational studies have examined the prevalence of PSD. The estimated prevalence of PSD in studies which employed screening of an entire stroke population have varied from 11% (House et al , 1991) to 63% (Gottlieb et al , 2002), with a mean prevalence of 19.3% for major depression, 18.5% for minor depression (Robinson, 2003) and an overall prevalence of any depressive disorder of 33% (Hackett and Anderson, 2005). What is not known is how commonly PSD is diagnosed and treated in actual clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…On n'a constaté aucune influence é vidente de l'appré ciation de l'humour Introduction Persistent poststroke depression (PSD) presents a special challenge, often adversely influencing recovery and mortality (Gottlieb et al, 2002;Nicholl et al, 2002;Gokkaya et al, 2005) and interpersonal relationships (Mukherjee et al, 2006;Haun et al, 2008). Les contrô les de dé pression aprè s accident cardio-vasculaire (n = 30) et rhumatismaux/orthopé diques (n = 30) ont é té comparé s au niveau de l'effet de l'induction verbale et non verbale d'humeur positive et neutre sur l'é tat de l'humeur, les attitudes interpersonnelles, l'angoisse psychologique et les autres dé ficiences de traitement cognitif et é motionnel connexes.…”
unclassified